Effects of natural antioxidants on the oxidative stability of waste cooking oil biodiesel. Issue 5 (28th May 2021) - J., Nagarajan; Narayanasamy, Bose
Abstract: The present study investigates the effect of natural antioxidants such as turmeric, cinnamon, black pepper, Red bell pepper, watermelon seed on the oxidation stability of Waste Cooking Oil biodiesel. The antioxidant capability of the selected antioxidants has been evaluated employing DPPH (2, 2-diphenyl-1-picrylhydrazyl) scavenging activity. The maximum percentage scavenging effect at 2500 ppm for the turmeric, cinnamon, black pepper, red bell pepper, and watermelon seed was found to be 92, 85, 88, 89 and 80 respectively. The presence of OH, RCOOH and phenolic compounds responsible for antioxidant activity was recorded by respective wave number by Fourier Transform Infrared Spectroscopy (FTIR). The phenolic content present in the natural antioxidant extracts was determined in terms of Gallic Acid Equivalent (GAE) using the Folin-Ciocalteu Test. The maximum value of GAE was recorded as 236.28 mg/g for Turmeric and minimum value as 101.14 mg/g for watermelon seed respectively. The antioxidant characteristics were evaluated through determination of oxidation stability of Waste Cooking Oil biodiesel and its antioxidant blends in terms of the stability period. It was observed that stability time increased with addition of antioxidants and found to be maximum for Turmeric extract as 18.61 h when compared to WCO biodiesel as 1.72 h.